Telkom Bandung vocational school scheduling application using a website-based genetic algorithm - Ramadhani, Putri; Nasir, Alfian; Abdullah, Zakia Mahbub; Novianty, Astri; Setianingsih, Casi (Universitas Telkom, 2025)
Scheduling is a very important factor for the learning process at school, it is also very important at SMK Telkom Bandung. At this school, the schedule is still done manually. Because of this, many problems occurred, there were schedule clashes and the teaching and learning process was hampered. Therefore, a scheduling system was created using a genetic algorithm which is one of the optimization algorithms and can be used in various case studies such as scheduling subjects at school. With the application of the genetic algorithm, it can produce an automatic and optimal subject schedule. From several trials on the genetic algorithm, the best fitness value is 1 with an average execution time of 14.42990657 seconds. The results of alpha testing and beta testing show that the website created is running well and is feasible to use. With this system, it is hoped that it will make it easier for admins, teachers and students to access schedules.